Avaliação institucional: um olhar sobre o processo de autoavaliação e sua relação com o comportamento empreendedor em uma IFES - Vale, Rosiane Rocha do (2014)
Evaluation in Higher Education Institutions in Brazil has gotten an important role in recent decades, and with the National Evaluation System of Higher Education Institutions SINAES, institutions have consolidated the evaluation model aiming at improving quality in higher education. The study was conducted with the objective of analyzing the managers of the Universidade Federal do Maranhão - UFMA perception of the institutional self-evaluation process, and its influence on entrepreneurial behavior in relation to this process. We used a mixed method, quantitative and qualitative, of exploratory type, and as research strategy, we used case study. For quantitative approach, McClelland s questionnaires about entrepreneurial behavioral characteristics were used aiming to identify entrepreneurial behavioral characteristics of the managers involved in the self-evaluation process. Forty-two managers, the coordinators of graduation courses and the academic centers directors participated in the study. Data were statistically analyzed with SPSS software version 18.0. Instrument s internal consistency was assessed by Cronbach's Alpha coefficient (0.88), attesting reliability and evaluation of the constructs. The found results verified that, on the profile characterization, there was a higher frequency of females; that the majority of respondents are aged 34-41; and that eight academic centers have participated in the survey, and that among them CCH and CCSO have obtained the higher respondents rates. Regarding graduation degrees, there were mainly doctors in management positions (61.9%) and most of them are in the institution for less than seven years. Regarding their involvement in the self-evaluation process, 52.4% are not involved in this process. The ten entrepreneurial behavioral characteristics have obtained medium and high intensity levels, among which we can highlight information searching that obtained 97.6%. From the entrepreneurial behavioral characteristics grouping, overall achievement group has obtained 90.5%; the planning group, 69.0%; and the power group, 90.5%. For qualitative data collection, we have conducted semi-structured interviews with five managers, from whom four were academic center directors and one a graduation course coordinator of UFMA. For data analysis, we adopted the content analysis using categorical and annunciation techniques. From this analysis, three categories have arisen, not a priori: institutional self-assessment process perception, participation in the process and self-evaluation process results perception. Approaches complementation - quantitative and qualitative - was accomplished through data triangulation. Results of data triangulation allowed us to verify the influence of entrepreneurial characteristics on perceptions of graduation course coordinators and academic centers directors in the selfevaluation process. The study results allowed us to know managers entrepreneurial characteristics and their relationship to their perceptions of institutional self-evaluation, so that these characteristics may contribute to the development of the institutional self-evaluation process at Universidade Federal do Maranhão.